2017
DOI: 10.1212/wnl.0000000000004365
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous immunoglobulin in myasthenia gravis exacerbation

Abstract: This study provides Class IV evidence that in patients with mild to moderate MG exacerbation, SCIg is safe and effective in reducing MG disability measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 24 publications
5
30
0
Order By: Relevance
“…Switching from IVIG to SCIG seems to be an effective strategy that attenuates immunoglobulin-induced adverse effects, especially for patients who have previously experienced severe adverse effects or are at high risk of developing adverse effects. An increasing number of well-designed studies show that SCIG can be used as a treatment for immunodeficiency diseases, multifocal motor neuropathy, chronic inflammatory demyelinating polyneuropathy, and myasthenia gravis ( 6 , 122 136 ) (Table 3 ). The results of two randomized, crossover studies indicate that the rate of systematic adverse effects was lower following SCIG than following IVIG, and no severe adverse effects were reported in patients treated with SCIG ( 123 , 135 ).…”
Section: Preventive Measuresmentioning
confidence: 99%
“…Switching from IVIG to SCIG seems to be an effective strategy that attenuates immunoglobulin-induced adverse effects, especially for patients who have previously experienced severe adverse effects or are at high risk of developing adverse effects. An increasing number of well-designed studies show that SCIG can be used as a treatment for immunodeficiency diseases, multifocal motor neuropathy, chronic inflammatory demyelinating polyneuropathy, and myasthenia gravis ( 6 , 122 136 ) (Table 3 ). The results of two randomized, crossover studies indicate that the rate of systematic adverse effects was lower following SCIG than following IVIG, and no severe adverse effects were reported in patients treated with SCIG ( 123 , 135 ).…”
Section: Preventive Measuresmentioning
confidence: 99%
“…A prospective, single‐center, open‐label study was recently published on the effects of SCIg in patients with mild to moderate gMG exacerbation 99 . Twenty‐two patients were included in the study and received 2‐g/kg dose of SCIg in a dose‐escalating manner over a 4‐week period.…”
Section: Recent and Ongoing Clinical Trials In Mgmentioning
confidence: 99%
“…Significant reductions were seen in the primary (QMG) and secondary (manual muscle testing, MG‐ADL, and MGC) endpoints at 6 weeks. High degree of satisfaction was reported on the Treatment Satisfaction Questionnaire for Medication (TSQM) in the domains of effectiveness, side effects, and convenience, and there were no serious side effects 99 …”
Section: Recent and Ongoing Clinical Trials In Mgmentioning
confidence: 99%
“…A retrospective cohort study indicated that a wide spectrum of MG patients, seropositive, seronegative, thymomatous, and with varying disease severity and duration, could be treated with SCIG or transitioned from IVIG to SCIG with clinical benefit, safety, and tolerability . A prospective open‐label trial found that in patients with a mild to moderate MG exacerbation, treatment with SCIG 0.5 g/kg weekly for 4 weeks leads to statistically significant clinical improvement at 6 weeks with most common side effects of mild headache and injection site reactions but with overall high degree of treatment satisfaction, safety, and tolerability …”
Section: Novel Immune‐based Therapeutic Approachesmentioning
confidence: 99%